The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3389/fmars.2021.706179
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Silica Nanoparticle on Growth Performance, Protein Digestibility, Hematology, Digestive Morphology, and Muscle Composition of Nile Tilapia, Oreochromis Niloticus

Abstract: The use of nanotechnology in food production systems is being investigated globally, though there is limited research on its effect on fish nutrition. Therefore, this study aimed to identify the effects of silica nanoparticles (NPs) on the nutrition and physiology of tilapia, Oreochromis niloticus. Four isonitrogenous diets (300 g/kg crude protein) with NPs (0, 1, 2, and 3 mg/kg diet) were fed to fish (6.52 ± 0.20 g) in a recirculatory aquaculture system for 56 days. Throughout the study period, the effects of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 101 publications
(110 reference statements)
0
6
0
Order By: Relevance
“…In addition, they have a higher bioavailability than typical metals of larger size and can detoxify heavy metals (Chen et al, 2022). Bashar et al (2021) aimed to study the effects of silica-NPs on the growth and nutrient digestibility of tilapia. They concluded that 2 mg/kg Si-NPs level improves the feed efficiency and hence apparent nutrient digestibility of fish also increases.…”
Section: Nutrient Absorptionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, they have a higher bioavailability than typical metals of larger size and can detoxify heavy metals (Chen et al, 2022). Bashar et al (2021) aimed to study the effects of silica-NPs on the growth and nutrient digestibility of tilapia. They concluded that 2 mg/kg Si-NPs level improves the feed efficiency and hence apparent nutrient digestibility of fish also increases.…”
Section: Nutrient Absorptionmentioning
confidence: 99%
“…In order to fulfill the need of micronutrients in aqua‐feeds, various metallic nanomaterials have been utilised, i.e. zinc‐NPs (SM Abdel‐Hammed et al, 2019), iron‐NPs (Akter et al, 2018), selenium‐NPs (Ghazi et al, 2022), silica‐NPs (Bashar et al, 2021), chromium‐NPs (Hussain et al, 2019) and silver‐NPs (Yin et al, 2020). In fish farming, anemia and poor growth result from iron deficiency.…”
Section: Introductionmentioning
confidence: 99%
“…In the industries of food production, NPs are playing a key role due to their nutritional and medical value [8] , [44] , [47] , [69] , [88] . The productivity of aquaculture can be enhanced by nanoparticles, by the activity of biomolecules with micronutrients [77] , [94] , along with the application of treatment of diseases without any negative impact to health of humans [39] .…”
Section: Introductionmentioning
confidence: 99%
“…More recently, SiNPs have been reported to stimulate immune parameters and enhance gene expression, and accordingly, antagonize the immune dysfunction and gene down-regulation elicited by A. veronii bacterial infection in C. gariepinus (Abdel Rahman et al 2023a ). Supplementing O. niloticus in SiNP-enriched diets boosts the ionic exchange mechanism and enhances growth efficacy and hematological picture indicated by augmenting growth indices and blood biomarkers (Alandiyjany et al 2021 ; Bashar et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%